Influence of restraint conditions on residual stress and distortion of 2219-T8 aluminum alloy TIG welded joints based on contour method. (August 2021) - Wang, Qiang; Zhao, Yue; Zhao, Tianyi; Yan, Dongyang; Wang, Guoqing; Wu, Aiping
Abstract: Residual stress is a severe problem concerning about the service life and the safety of welded structures, which is affected by the assembling and restraint conditions. In this study, the residual stresses of 2219-T8 aluminum alloy butt-welded joints are investigated at different restraint conditions through contour method, which can obtain the 2D map of residual stress on the cross-sectional surface of the weld joints. X-ray diffraction measurement method is used to compare the results of the contour method. The results show that the variation trend and distribution of the residual stresses obtained by contour method are in good agreement with the results tested by X-ray diffraction method. The maximum internal residual stress, which locates in the middle thickness and the HAZ, is higher than that on the surfaces, with a difference over 50 MPa. The restraint conditions that mentioned in this study affect the amplitude of the tensile residual stresses and their distributions. Little influence is found on the amplitude of the internal residual stresses. But the surface residual stress is affected by restraint conditions. Higher vertical pressing force results in larger tensile stress region and larger distance between peak tensile stress and the weld center. Higher horizontal clamping force induces a smaller tensile stress region and a steeper variation rate of tensile stress in the HAZ. With higher vertical pressing force and lower horizontal clamping force, the welded joint obtains a smaller angular distortion. Highlights: The 2D map of the longitudinal residual stress is obtained by contour method on the cross-section of the weld joints. The results obtained by contour method are in good agreement with that of XRD method. Restraint conditions affect the amplitude of the tensile residual stresses and their distributions. Vertical pressing force prevents angular deformation. Horizontal clamping force, however, has opposite effect.